GAMBARAN KARAKTERISTIK DEMOGRAFI, JENIS, DAN DURASI PEMERIKSAAN PSIKIATRI UNTUK KEPENTINGAN PENEGAKAN HUKUM PIDANA DI RSJD ATMA HUSADA MAHAKAM SAMARINDA TAHUN 2018-2022 - Saputri, Ni Made Maharani Indira; Danial; Nugrahayu, Eka Yuni (Jurnal Medika : Karya Ilmiah Kesehatan, 2026)
A criminal act can be committed by someone who has a mental disorder. A psychiatric examination can be carried out at the request of an investigator to determine whether a person who has committed a crime is influenced by the mental disorder he is experiencing. This study aims to provide an overview of the education, occupation, marital status, type of examination request, and duration of examination of psychiatric examinations conducted for criminal law enforcement purposes at RSJD Atma Husada Mahakam Samarinda from 2018 to 2022. This study was a retrospective descriptive study. The research data were collected from medicolegal sources, including Psychiatric Health Certificates (SKKJ) and Visum et Repertum Psychiatricum (VeRP), as well as the medical records of the individuals under examination. The total sampling method was employed, yielding a total of 69 samples. The research results showed that 49.3% examinees were not working. The largest ethnic groups were Banjar and Bugis (23.2%). The highest marital status was married (58%). The largest type of examination request was SKKJ (92.8%). A majority of the examined individuals, specifically 66.7%, received inpatient care for a duration of two weeks or less.